The Role of Human Papilloma Virus in Synchronous Gynecologic Malignancies: A Report of Two Cases and Review of the Literature - Salih Taşkın; Emre Göksan Pabuçcu; Alper Kahraman; İbrahim Yalçın; Uğur Fırat Ortaç (Gynecology Obstetrics & Reproductive Medicine)
Aim of the paper is to investigate the suspicious role of HPV in synchronous endometrial and cervical carcinomas and to discuss the relation between HPV and endometrium epithelium. The first case is 68- year-old and the second case is 56 year-old postmenopausal woman who were diagnosed with invasive cervical carcinoma synchronously with endometrial carcinoma. Following surgical procedures, high risk HPV DNA analysis using PCR were undertaken in both cases to investigate the possible role of HPV in synchronous malignancies. All endometrial samples were considered as negative for high risk HPV types however all cervical samples were considered as positive. Unlike cervical pathologies, HPV does not seem to play active role as etiologic agent in endometrial neoplasms, even detected synchronously with invasive cervical cancers.